2015
DOI: 10.15740/has/ijpp/8.1/7-12
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of new chemistry molecules against sucking pests of Bt transgenic cotton

Abstract: Studies were conducted to evaluate some new chemistry insecticide molecules as foliar application for their bioefficacy against major sucking pests and toxicity against predators of Bt transgenic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
4
8
0
Order By: Relevance
“…On the other hand, the tested insecticides were more effective against immature stages than adults B. tabaci, our study proved that imidacloprid, flonicamid and dinotefuran were higher significant in suppressing populations of B. tabaci. These results are consistent with data reported by that (Kalyan et al,2012;Gourkhede et al, 2015 andGhelani et al,2014) who reported that flonicamid and imidacloprid were effective against B. tabaci in cotton fields. Also, Roditakis et al, 2014;Sathyan et al, 2016 andNemade et al, 2017 found that flonicamid at rate 75 g a.i./ha and flonicamid at 100 g a.i./ha and imidacloprid managed B. tabaci populations.…”
Section: Efficacy Of Tested Insecticides Against Bemisia Tabaci (Genn)supporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the tested insecticides were more effective against immature stages than adults B. tabaci, our study proved that imidacloprid, flonicamid and dinotefuran were higher significant in suppressing populations of B. tabaci. These results are consistent with data reported by that (Kalyan et al,2012;Gourkhede et al, 2015 andGhelani et al,2014) who reported that flonicamid and imidacloprid were effective against B. tabaci in cotton fields. Also, Roditakis et al, 2014;Sathyan et al, 2016 andNemade et al, 2017 found that flonicamid at rate 75 g a.i./ha and flonicamid at 100 g a.i./ha and imidacloprid managed B. tabaci populations.…”
Section: Efficacy Of Tested Insecticides Against Bemisia Tabaci (Genn)supporting
confidence: 93%
“…Therefore, it is imperative to search out some alternatives of highly toxic insecticides and safe to humans and nontoxic to the natural enemies. In this view, there is a field of utilizing the newer chemistry molecules such as pyridinecarboxamide and neonicotinoid which are required in small quantity and economically effective for control of sucking pests in cotton ecosystem (Gourkhede et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The present investigations are in line with the outcome of Ghelani et al, (2014) they also reported that the treatments with flonicamid, acetamiprid, thiamethoxam caused significantly maximum mortality of aphids. Gaurkhede et al, (2015) observed minimum aphid population in the plots treated with flonicamid 50 WG @ 0.02 per cent (2.96 aphids/ leaf) and was at par with dinotefuran 20 SG @ 0.008 (3.50 aphids / leaf). Sathyan et al, (2016) reported that quinalphos 25 EC and flubendiamide 20 WG were found to be less effective against aphid population.…”
Section: Aphidsmentioning
confidence: 83%
“…Present study results are in close agreement with findings of Bhavani Sankara Rao et al, (1991) and Ghelani et al, (2006) they also reported that bio pesticides (botanicals and microbials) were less effective over the chemical pesticides against sucking pests of okra. Gaurkhede et al, (2015) reported that fipronil 5 SC, flonicamid 50 WG, dinotefuran 20 SG and acetamiprid 20 SP effectively minimized the thrips density. Ghelani et al, (2014) and Ravikumar et al, (2016) observed maximum mortality of thrips with flonicamid 50 WG.…”
Section: Thripsmentioning
confidence: 99%
See 1 more Smart Citation